Do founders attribute their success to skill or luck? - Benjamin J. Lough; Alyssa McFadden (Journal of Innovation and Entrepreneurship, 2023)
This study analyzes transcripts derived from 183 podcast interviews that ask successful entrepreneurs whether luck or skill and hard work account for their success. It quantitatively disaggregates founders' answers to this standard question based on differences in their gender, race, and geography of their birth. Qualitative analysis further considers the degree to which founders' perspectives might be associated with an internalized locus of control and their social positioning, alongside their identities and belief systems. Results indicate differences across gender, but no strong evidence of difference was evident by race and geography. Thematic analysis of transcripts revealed several additional determinants that founders attributed to their success. By investigating the lived experiences of successful founders disaggregated by gender, race, and geography, this study sheds light on how diverse founders attribute their success to various internal and external forces.
Keywords: 650; Entrepreneurship; Intersectionality; Locus of control; Luck; Skill